SOLUSI CERDAS MENYUSUN LAPORAN PERTANGGUNGJAWABAN KOPERASI DENGAN PENERAPAN E-KOPERASI - Rahayu, Yuri; Sriyadi, Sriyadi; Ramdhani, Lis Saumi; Bahri, Saeful (Jurnal Ilmu Ekonomi dan Pembangunan, 2017)
The ease with which to prepare an Accountability Report is a wish that cooperative management wishes to undertake. Difficulties that have been faced in preparing the report resulted in the health assessment of cooperatives can not be fulfilled resulting in the level of assessment and the status of cooperatives become inactive. Selection of smart and proper cooperative management system will result in more productive and quality performance, so it needs an E-Cooperative System that can further facilitate the performance of the boards utilizing Information Technology that is able to facilitate the preparation of accountability report of the board effectively and efisein. The research method is development research that is research method used to produce certain product. Results of Implementation of E-Cooperatives in Prosperous Cooperatives PKK RW VI Kel. Tipar Kota Sukabumi produces a qualified Accountability Report and qualifies a cooperative health assessment and is able to streamline the performance of the board, so it is expected that the implementation of this E-Koperasi system can provide solutions to the Savings and Loan Partnership managers, especially in the Sukabumi area and announced throughout Indonesia Simplify the Accountability Report. Keywords: Smart Solution, E-Cooperative Application, Accountability Reporting